UJI AKTIVITAS EKSTRAK BUNGA KECOMBRANG (Etlingera elatior Jack) SEBAGAI HIPOLIPIDEMIA PADA TIKUS WISTAR OBESITAS - Sri Wardani; Ni Wayan Bogoriani; Ni Luh Rustini (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2022)
Kecombrang (Etlingera elatior Jack) is a plant that has potential for hypolipidemia. Kecombrang has secondary metabolites consisting of tannins, saponins, alkaloids, steroids, terpenoids, phenolics, and flavonoids. The purpose of this study was to determine the hypolipidemic activity of kecombrang flower methanol extract in obesed Wistar rats fed a high-fat diet. The test animals used in this study were 18 female white rats aged two months, weight of ± 150 grams. The test animals were divided into three groups, namely normal control (only given standard feed), high-fat control (obesed rats with high-fat diet), and flower treatment group (obesed rats with a high-fat diet + flower methanol extract 100 mg/kgBW) orally for 30 days. The results showed that kecombrang flowers reduced total cholesterol levels by 55.5%, triglycerides (TG) by 57.4%, LDL by 76.73%, and increased HDL by 42.96%. The kecombrang flower has the potential for hypolipidemia which is characterized by a decrease in total cholesterol, TG, LDL, and can increase HDL levels in obese rats significantly (p<0.05).